Sherard Cowper-Coles, Cables from Kabul: Inside Story of West Afghanistan’s Campaign - Mr. Sajid Aziz (CISS Insight Journal, 2015)
The book ‘Cables from Kabul’ is a memoir-cum-diplomatic account by Sherard CowperColes, Britain’s former ambassador to Afghanistan. Slyly titled, this book sheds fleeting light on a whole range of issues-drugs, COIN, the ever-elusive peace process, policy discussion within ISAF and NATO forces and the humdrum of life in Afghanistan, turned occasionally into a squib courtesy to his immaculate prose, et al; that afflict the troubled land of Afghanistan. This three hundred page work is divided into 5 parts; though published in 2011, its relevance as an account, a relatively and coyly honest one at that, from an insider helps readers to broaden, substantiate and at times to rebut the prevalent perceptions about the situation in Afghanistan. Cables from Kabul helps us understand how West descended into the abyss and quagmire of Afghanistan and how can this situation be ameliorated, paving the way out for the foreign forces. Plethora of themes, corresponding with the experience and the subsequent impressions of the author, dot the canvas of this account. The spectrum ranges from the contemporary logic of COIN and its insufficiency to the failure of efforts to eradicate drugs from Afghanistan, from the motives of invasion to historical innuendos and allusions to the invaders of Afghanistan of yesteryears. Sherard’s first-hand information is, more often than not, interspersed with insightful analysis emanating from a profound interest in history, evidenced by his references to Peloponnesian War, Thucydides, and the putsch of Shinwari tribe against King Amanuallah, Livy and his book ‘History of Rome.’ Though his dilation on the given themes fallscomes well short of the so-called academic standard, but they are no less useful for understanding the war in Afghanistan.